Efficient education policy: A second-order elasticity rule - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2010)
Assuming a two-period model with endogenous choices of labour, education, and saving, efficient education policy is characterized for a Ramsey-like scenario in which the government is constrained to use linear instruments. It is shown that education should be effectively subsidized if, and only if, the elasticity of the earnings function is increasing in education. The strength of second-best subsidization increases in the elasticity of the elasticity of the earnings function. This second-order elasticity rule extends the well-known Ramsey-Boiteux Inverse Elasticity Rule.
Keywords: H21; I28; J24; 330; endogenous choice of education; labour; and saving; second-best efficient taxation; linear instruments; finite periods; Ramsey's Rule; Inverse Elasticity Rule; Bildungspolitik; Subvention; Optimale Besteuerung; Bildungsverhalten; Einkommensfunktion; Elastizität; Theorie